Exploring the association between Th17 pathway gene polymorphisms and pulmonary tuberculosis - Li, Hong-Miao; Wang, Li-Jun; Huang, Qian; Pan, Hai-Feng; Zhang, Tian-Ping (Frontiers in Immunology, 2022)
Th17 cells play a key role in immunity against Mycobacterium tuberculosis (MTB), and this study aimed to explore the association of Th17 pathway gene polymorphisms with pulmonary tuberculosis (PTB) susceptibility in a Chinese population. A total of 10 single nucleotide polymorphisms in Th17 pathway genes (IL-17A gene rs2275913, rs3748067, rs8193036, rs3819024, IL-17F gene rs7741835, rs763780, IL-21 gene rs907715, rs2055979, IL-23R gene rs11805303, and rs7518660) were genotyped in 456 PTB patients and 466 controls using SNPscan technique. The IL-23R rs11805303 CC genotype, C allele frequencies were significantly lower in PTB patients than in controls, and the rs11805303 variant was significantly associated with the reduced risk of PTB in a recessive model. There were no significant associations between IL-17A, IL-17F, and IL-21 gene variations and PTB risk. In IL-17A gene, rs2275913, rs3748067, and rs3819024 variants were associated with drug resistance in PTB patients. In IL-17F gene, rs7741835 variant affected drug resistance, and rs763780 variant was associated with hypoproteinemia in PTB patients. In addition, the lower frequencies of the TT genotype, T allele of rs2055979 were found in PTB patients with drug-induced liver injury. Haplotype analysis showed that IL-23R CG haplotype frequency was significantly lower in PTB patients than in controls, while the TG haplotype frequency was higher. In conclusion, IL-23R rs11805303 polymorphism may contribute to the genetic underpinnings of PTB in the Chinese population, and the IL-17A, IL-17F, and IL-21 genetic variations are associated with several clinical manifestations of PTB patients.